DAKWAH MITIGASI BENCANA BANJIR OLEH TOKOH AGAMA DI KECAMATAN RUPIT KABUPATEN MURATARA - Charel Karina Marlin Rades; Silfia Hanani; Gazali Gazali; Darul Ilmi (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This study aims to explore the contribution of religious leaders in implementing da'wah (Islamic outreach) oriented toward flood mitigation in Rupit District, North Musi Rawas Regency. The frequent flooding in this area not only causes physical and economic losses but also impacts the social and spiritual well-being of the community. In this context, religious leaders play a crucial role as agents of change, capable of raising awareness, instilling religious values, and guiding the community to be alert and wise in facing the threat of disaster. The study used a qualitative approach, collecting data through observation, interviews, and documentation with religious leaders and local residents. The research findings revealed that da'wah conducted by religious leaders emphasized three main aspects: (1) raising awareness of environmental sustainability as part of religious teachings, (2) internalizing the values ​​of patience, solidarity, and social awareness in the face of disasters, and (3) encouraging community preparedness through preventive measures and active involvement in mitigation efforts. Thus, the da'wah of religious leaders is not only spiritual in nature but also serves as an effective social instrument in strengthening community resilience in the face of flooding in Rupit District.